2023
DOI: 10.3390/ph16030385
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tocotrienol in Arthritis Management—A Scoping Review of Literature

Abstract: Arthritis is a cluster of diseases impacting joint health and causing immobility and morbidity in the elderly. Among the various forms of arthritis, osteoarthritis (OA) and rheumatoid arthritis (RA) are the most common. Currently, satisfying disease-modifying agents for arthritis are not available. Given the pro-inflammatory and oxidative stress components in the pathogenesis of arthritis, tocotrienol, a family of vitamin E with both anti-inflammatory and antioxidant properties, could be joint-protective agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Furthermore, there are also available reviews that explore the potential mechanisms of tocotrienol in mitigating glucocorticoid-induced osteoporosis, drawing from existing in vivo and in vitro findings ( Ekeuku et al, 2022 ). In a more recent article published by Singh et al, they conducted a scoping review specifically focusing n the impact of tocotrienol on arthritis ( Tejpal Singh et al, 2023 ). According to the solitary clinical trial uncovered in the existing body of literature, palm tocotrienol could potentially enhance joint function in individuals with osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are also available reviews that explore the potential mechanisms of tocotrienol in mitigating glucocorticoid-induced osteoporosis, drawing from existing in vivo and in vitro findings ( Ekeuku et al, 2022 ). In a more recent article published by Singh et al, they conducted a scoping review specifically focusing n the impact of tocotrienol on arthritis ( Tejpal Singh et al, 2023 ). According to the solitary clinical trial uncovered in the existing body of literature, palm tocotrienol could potentially enhance joint function in individuals with osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the solitary clinical trial uncovered in the existing body of literature, palm tocotrienol could potentially enhance joint function in individuals with osteoarthritis. The author’s conclusion highlights tocotrienols as a promising candidate for its potential role as an anti-arthritic agent ( Tejpal Singh et al, 2023 ). Many recent review papers tend to have a narrower focus, concentrating on specific musculoskeletal conditions rather than addressing the broader spectrum of challenges related to musculoskeletal health.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that δ-tocotrienol (δTE) supplementation reduced heart and liver inflammation in obese rats [ 37 ]. Our group has previously reported the anti-osteoporotic and anti-arthritic properties of tocotrienol [ 38 , 39 , 40 , 41 ]. Tocotrienol was also shown to enhance the efficacy of daptomycin against methicillin-resistant Staphylococcus aureus in an infected wound model [ 42 ].…”
Section: Introductionmentioning
confidence: 99%